2022
DOI: 10.1128/aac.02067-21
|View full text |Cite
|
Sign up to set email alerts
|

Selection of AmpC β-Lactamase Variants and Metallo-β-Lactamases Leading to Ceftolozane/Tazobactam and Ceftazidime/Avibactam Resistance during Treatment of MDR/XDR Pseudomonas aeruginosa Infections

Abstract: Infections caused by ceftolozane/tazobactam and ceftazidime/avibactam-resistant P. aeruginosa infections are an emerging concern. We aimed to analyze the underlying ceftolozane/tazobactam and ceftazidime/avibactam resistance mechanisms in all MDR/XDR P. aeruginosa isolates recovered during one year (2020) from patients with a documented P. aeruginosa infection. Fifteen isolates showing ceftolozane/tazobactam and ceftazidime/avibactam resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Although these therapies displayed encouraging levels of effectiveness from the first moment, P. aeruginosa has repeatedly shown the capacity to develop resistance to CAZ-AVI and TOL-TAZ through different mechanisms, posing a real danger to the long-term efficacy of these drugs. In this sense, the acquisition of class B carbapenemases is one of the most threatening mechanisms since only cefepime-taniborbactam retains activity against VIM/NDM-producing P. aeruginosa strains ( 27 , 54 , 56 ). However, there are also some mutation-driven mechanisms, such as the selection of changes in ampC and its regulatory genes, that enable the hyperproduction of the enzyme together with an increase in its cephalosporin hydrolysis capacity (obviously including CAZ and TOL) and resistance to inhibition by avibactam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these therapies displayed encouraging levels of effectiveness from the first moment, P. aeruginosa has repeatedly shown the capacity to develop resistance to CAZ-AVI and TOL-TAZ through different mechanisms, posing a real danger to the long-term efficacy of these drugs. In this sense, the acquisition of class B carbapenemases is one of the most threatening mechanisms since only cefepime-taniborbactam retains activity against VIM/NDM-producing P. aeruginosa strains ( 27 , 54 , 56 ). However, there are also some mutation-driven mechanisms, such as the selection of changes in ampC and its regulatory genes, that enable the hyperproduction of the enzyme together with an increase in its cephalosporin hydrolysis capacity (obviously including CAZ and TOL) and resistance to inhibition by avibactam.…”
Section: Discussionmentioning
confidence: 99%
“…In light of all of these antecedents, knowledge gaps, and the increasing appearance of mutations enabling enzyme variants that provide resistance to new β-lactam–β-lactamase inhibitor combinations such as ceftazidime-avibactam (CAZ-AVI) and ceftolozane-tazobactam (TOL-TAZ) ( 26 31 ), which are two of our last resources to combat P. aeruginosa at present, here, we intended to further dissect the biological cost associated with AmpC-type enzyme production. For this purpose, by site-directed mutagenesis, we assessed the role of AmpC β-lactamase activity per se in the virulence attenuation associated with its hyperproduction, providing clues to the pathways through which this enzyme is able to dampen bacterial fitness.…”
Section: Introductionmentioning
confidence: 99%
“…This agreement between our results and those reported by Grupper et al ( Grupper et al, 2017 ) could be partially explained by the increased repertoire of beta-lactam resistance mechanisms in our XDR (all of them with CR phenotype) and DTR (resistant to all the beta-lactams and quinolones analyzed) isolates. Indeed, it has been shown that mechanisms usually associated with beta-lactam and carbapenem resistance ( Moya et al, 2012 ; Castanheira et al, 2014 ; Cabot et al, 2018 ; Ruedas-Lopez et al, 2022 ) are also implicated in resistance to CZA ( Chalhoub et al, 2018 ; Sanz-Garcia et al, 2018 ; Castanheira et al, 2019 ) and, to a lesser extent, to C/T ( Cabot et al, 2014 ; Wi et al, 2018 ; Fournier et al, 2021 ; Ruedas-Lopez et al, 2022 ). Accordingly, the high difference here reported between CZA and C/T activity in DTR isolates, a category that have not been previously considered in this kind of studies ( Del Barrio-Tofino et al, 2017 ; Grupper et al, 2017 ; Pfaller et al, 2017 ; Wi et al, 2018 ; Sader et al, 2021 ; Torrens et al, 2022 ), evidencing that the effectiveness of CZA treatment could be compromised in this group of strains.…”
Section: Discussionmentioning
confidence: 99%
“…Despite CZA and C/T presenting a high activity rate and good coverage against P. aeruginosa clinical isolates, including MDR and CRPA strains ( Goodlet et al, 2016 ; Pfaller et al, 2017 ; Pfaller et al, 2018 ; Horcajada et al, 2019 ; Sader et al, 2021 ), some acquired resistance mechanisms to these antibiotic combinations have been observed. It has been reported that resistance to both drugs may be developed through mutation of penicillin-binding proteins (PBPs) ( Castanheira et al, 2019 ; Fournier et al, 2021 ); by horizontally-transferred beta-lactamases ( Ortiz de la Rosa et al, 2019 ; Arca-Suarez et al, 2021 ; Fraile-Ribot et al, 2021 ; Teo et al, 2021 ; Poirel et al, 2022 ; Ruedas-Lopez et al, 2022 ); or by overexpression and/or structural modifications in the Ω-loop region of the chromosomally-encoded beta-lactamase, AmpC ( Cabot et al, 2014 ; Fraile-Ribot et al, 2017 ; Cabot et al, 2018 ; Chalhoub et al, 2018 ; Arca-Suarez et al, 2020 ; Compain et al, 2020 ; Teo et al, 2021 ; Ruedas-Lopez et al, 2022 ). In addition, mutations leading to overexpression and/or structural modification of the resistance-nodulation-division (RND) efflux system, MexAB-OprM, are associated with resistance to CZA ( Chalhoub et al, 2018 ; Sanz-Garcia et al, 2018 ; Castanheira et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among P. aeruginosa isolates, deletions of various sizes in the Ω-loop region of chromosomal AmpC gene can result in CZA resistance by changing the avibactam binding pocket region of AmpC β-lactamases [ 166 ]. In addition, the administration of CZA and ceftolozane-tazobactam has a potential to select MDR P. aeruginosa strains—producing metallo-beta-lactamases (MBLs) and Pseudomonas-derived cephalosporinase (PDC) variants [ 167 ]. Xu et al also revealed conjugative plasmid-mediated bla CMY-172 -associated CZA resistance in clinical KPC-carrying K. pneumoniae strains [ 168 ].…”
Section: Novel Blblismentioning
confidence: 99%